GE_GERICHTE PS/55/2022 vom 25. Juli 2021 - GE Cour de justice (2021)
MESURE THÉRAPEUTIQUE INSTITUTIONNELLE;SOINS MÉDICAUX;COMPÉTENCE RATIONE MATERIAE;PLACEMENT À DES FINS D'ASSISTANCE | CP.59.al2; LS.50; LS.51